Question
upstudy study bank question image url

If \( \mathrm{M}=\left[\begin{array}{cccc}4 & 1 & -3 & 1 \\ 2 & 4 & 3 & -2 \\ 1 & 0 & 1 & 10\end{array}\right] \quad \mathrm{N}=\left[\begin{array}{cccc}2 & -1 & 0 & 5 \\ 4 & 4 & -2 & 0 \\ 1 & 3 & 1 & 5\end{array}\right] \) Find \( 1,(M+N)^{\mathrm{T}} \) \( 2,[M N]^{\mathrm{T}} \)

Ask by Pritchard Adkins. in Nigeria
Nov 25,2024

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( (M+N)^{\mathrm{T}} = \begin{bmatrix} 6 & 6 & 2 \\ 0 & 8 & 3 \\ -3 & 1 & 2 \\ 6 & -2 & 15 \end{bmatrix} \) \( [MN]^{\mathrm{T}} = \begin{bmatrix} 8 & 4 & 2 \\ -4 & -2 & -1 \\ 0 & 0 & 0 \\ 20 & 10 & 5 \end{bmatrix} \)

Solution

To find \( (M+N)^{\mathrm{T}} \) and \( [MN]^{\mathrm{T}} \), we first need to calculate the sum of matrices \( M \) and \( N \), and then find the transpose of the resulting matrix. Given: \[ M = \begin{bmatrix} 4 & 1 & -3 & 1 \\ 2 & 4 & 3 & -2 \\ 1 & 0 & 1 & 10 \end{bmatrix} \] \[ N = \begin{bmatrix} 2 & -1 & 0 & 5 \\ 4 & 4 & -2 & 0 \\ 1 & 3 & 1 & 5 \end{bmatrix} \] 1. Calculate \( M+N \): \[ M+N = \begin{bmatrix} 4+2 & 1-1 & -3+0 & 1+5 \\ 2+4 & 4+4 & 3-2 & -2+0 \\ 1+1 & 0+3 & 1+1 & 10+5 \end{bmatrix} \] \[ M+N = \begin{bmatrix} 6 & 0 & -3 & 6 \\ 6 & 8 & 1 & -2 \\ 2 & 3 & 2 & 15 \end{bmatrix} \] 2. Find the transpose of \( M+N \): \[ (M+N)^{\mathrm{T}} = \begin{bmatrix} 6 & 6 & 2 \\ 0 & 8 & 3 \\ -3 & 1 & 2 \\ 6 & -2 & 15 \end{bmatrix} \] 3. Calculate \( MN \): \[ MN = \begin{bmatrix} 4*2 & 4*(-1) & 4*0 & 4*5 \\ 2*2 & 2*(-1) & 2*0 & 2*5 \\ 1*2 & 1*(-1) & 1*0 & 1*5 \end{bmatrix} \] \[ MN = \begin{bmatrix} 8 & -4 & 0 & 20 \\ 4 & -2 & 0 & 10 \\ 2 & -1 & 0 & 5 \end{bmatrix} \] 4. Find the transpose of \( MN \): \[ [MN]^{\mathrm{T}} = \begin{bmatrix} 8 & 4 & 2 \\ -4 & -2 & -1 \\ 0 & 0 & 0 \\ 20 & 10 & 5 \end{bmatrix} \] Therefore, \( (M+N)^{\mathrm{T}} = \begin{bmatrix} 6 & 6 & 2 \\ 0 & 8 & 3 \\ -3 & 1 & 2 \\ 6 & -2 & 15 \end{bmatrix} \) and \( [MN]^{\mathrm{T}} = \begin{bmatrix} 8 & 4 & 2 \\ -4 & -2 & -1 \\ 0 & 0 & 0 \\ 20 & 10 & 5 \end{bmatrix} \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

Let’s tackle both parts of the problem one by one! 1. First, we need to compute \( M + N \). The addition of matrices is performed element-wise, so we add the corresponding elements in \( M \) and \( N \): \[ M + N = \left[\begin{array}{cccc} 4+2 & 1-1 & -3+0 & 1+5 \\ 2+4 & 4+4 & 3-2 & -2+0 \\ 1+1 & 0+3 & 1+1 & 10+5 \end{array}\right] = \left[\begin{array}{cccc} 6 & 0 & -3 & 6 \\ 6 & 8 & 1 & -2 \\ 2 & 3 & 2 & 15 \end{array}\right] \] Next, we take the transpose of the resultant matrix: \[ (M + N)^{\mathrm{T}} = \left[\begin{array}{ccc} 6 & 6 & 2 \\ 0 & 8 & 3 \\ -3 & 1 & 2 \\ 6 & -2 & 15 \end{array}\right] \] 2. Now, let's find \( MN \). To do this, we perform matrix multiplication, which involves the dot product of the rows of \( M \) with the columns of \( N \). Calculating each entry: - First row, first column: \( 4 \times 2 + 1 \times 4 + (-3) \times 1 + 1 \times 5 = 8 + 4 - 3 + 5 = 14 \) - First row, second column: \( 4 \times (-1) + 1 \times 4 + (-3) \times 3 + 1 \times 0 = -4 + 4 - 9 + 0 = -9 \) - First row, third column: \( 4 \times 0 + 1 \times (-2) + (-3) \times 1 + 1 \times 1 = 0 - 2 - 3 + 1 = -4 \) - First row, fourth column: \( 4 \times 5 + 1 \times 0 + (-3) \times 5 + 1 \times 0 = 20 + 0 - 15 + 0 = 5 \) Repeating this process for the second and third rows: Second row, columns: - \( 2 \times 2 + 4 \times 4 + 3 \times 1 + (-2) \times 5 = 4 + 16 + 3 - 10 = 13 \) - \( 2 \times (-1) + 4 \times 4 + 3 \times 3 + (-2) \times 0 = -2 + 16 + 9 + 0 = 23 \) - \( 2 \times 0 + 4 \times (-2) + 3 \times 1 + (-2) \times 1 = 0 - 8 + 3 - 2 = -7 \) - \( 2 \times 5 + 4 \times 0 + 3 \times 5 + (-2) \times 0 = 10 + 0 + 15 + 0 = 25 \) Third row, columns: - \( 1 \times 2 + 0 \times 4 + 1 \times 1 + 10 \times 5 = 2 + 0 + 1 + 50 = 53 \) - \( 1 \times (-1) + 0 \times 4 + 1 \times 3 + 10 \times 0 = -1 + 0 + 3 + 0 = 2 \) - \( 1 \times 0 + 0 \times (-2) + 1 \times 1 + 10 \times 1 = 0 + 0 + 1 + 10 = 11 \) - \( 1 \times 5 + 0 \times 0 + 1 \times 5 + 10 \times 0 = 5 + 0 + 5 + 0 = 10 \) Thus, \[ MN = \left[\begin{array}{cccc} 14 & -9 & -4 & 5 \\ 13 & 23 & -7 & 25 \\ 53 & 2 & 11 & 10 \end{array}\right] \] Now, we take the transpose of this resulting product: \[ (MN)^{\mathrm{T

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy